PENGARUH FAKTOR SOSIAL, PRIBADI, DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN TIKET TEATER JKT48 DENGAN BRAND LOVE SEBAGAI VARIABEL INTERVENING - Margaretha, Margaretha; Iskandar, Donant Alananto (Economic Faculty, Attahiriyah Islamic University, 2018)
The purpose of this research is to understand the influence of social, personal, and psychological factors towards purchase decision of JKT48 Theater’s Tickets. Data were collected from 126 fans of JKT48 in DKI Jakarta who have bought tickets three times or more. The result of this research shows that psychological factors significantly influence the purchase decision. Brand love moderates the relationship of all independent variables with the dependent variables. The existence of brand love as a moderating variable will weaken the influence of social factors on purchasing decisions. The implications of this research can be a reference for the management team in formulating JKT48 Theater’s Tickets sales strategy related to social, personal, and psychological factors. Keywords: social,brand love, purchase decision